The Study of Influence of High Pressure Torsion Process on Acoustic Emission Activity of Compressed Mg-Li Alloys - RANACHOWSKI, Zbigniew; RANACHOWSKI, Przemysław; REJMUND, Feliks; PAWEŁEK, Andrzej; PIĄTKOWSKI, Andrzej; JASIEŃSKI, Zdzisław (Archives of Acoustics, 2008)
In this paper the application of acoustic emission (AE) method is presented to recognize changes of properties of light alloys subjected to large plastic deformations. Measurements were performed on three alloy compositions: Mg10Li, Mg10Li1Al and Mg10Li5Al. Problems related to small dimensions of the samples and low energy of acoustic signals were overcome using the channel-die system to monitor AE effects of compressed samples. As a result of the applied high pressure torsion (HPT) process a strong grain size reduction effect occurred in tested materials. Dimensions of grains diminished considerably resulting in the decrease of the registered AE event rate by almost an order of magnitude.